Initial Study On Safety Hazards by Heavy Transportation On Malaysian Roads - Md Yusof, Hasrul Izatie; Shamsudin, Shamsul Anuar; A.Rahman, Norasra; Zainal, Zairulazha; Al_Issa, Huthaifa Ahmad (International Journal of Integrated Engineering, 2022)
A pilot study was done to evaluate the road safety in Malaysia that is related to heavy transportation. The project consisted of survey, analytical calculations, and computer simulations. The survey was conducted to investigate the use of current active safety features like the warning signs, which include lights, light reflective stickers, and the color of canvas used on heavy vehicles. Fortunately, light reflective stickers could be an aid to passively illuminate the heavy vehicles. The slow speed like 40 km/h commonly maintained by heavy vehicles when climbing up hills with heavy load is a hazard since being too slow may cause a more severe rear-end collision damage. Additionally, computer impact analyses were also done by using ABAQUS, where several collisions between a car and a heavy vehicle were studied. Hence, the conclusion can be made that the slower the speed of a heavy vehicle, the higher the stress experienced by the car colliding from behind the truck. It is recommended that the truck has about 376 kW power to pull a maximum load of 36,000 kg. Trucks are also suggested to maintain at least 60 km/h speed during hill climbing with a much lower load.